Presenting Materials for Grammar Instruction: An Analysis of Current English Language Textbooks in Sri Lankan universities - Radeeshanika Basnayake, Lakmini (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2021)
The aim of this paper is to analyse the use of materials for grammar instruction in two English language textbooks practised for the compulsory English language programme conducted by Department of English Language Teaching at Sabaragaamuwa University, Sri Lanka. In this regard, the study questions as to what extent do the materials used for grammar teaching in the textbooks provide learners opportunities to use the language meaningfully in real life situations. To answer this question, the study carried out a detailed content analysis of the manner in which the grammar tasks have been presented in the two textbooks used for the first year students: Communicate in English Year I Semester I and Communicate in English Year I Semester II. Qualitative content analysis was carried out as the methodology of data analysis. The results revealed that the manner of presenting materials for grammar in both textbooks do not motivate students using the target language relevant to the real life situations in meaningful contexts, as both textbooks provide grammar structures in a prescriptive way through explicit grammar instruction. Thus, the study concluded that the two textbooks should be modified in presenting materials of grammar; explicit descriptions of grammar rules and prescriptive mode with mechanical grammar exercises should be replaced by authentic materials for grammar instruction which can provide many opportunities to use the target language in real life contexts. Key Words: English, Textbooks, presenting materials, grammar in context